Publication bias in pediatric emergence delirium: a cross-sectional analysis of ClinicalTrials.gov and ClinicalTrialsRegister.eu - Meyburg, Jochen; Ries, Markus (BMJ open, 2020)
Objectives Emergence delirium (ED) is a frequent and potentially serious complication of general anaesthesia in children. Although there are various treatment strategies, no general management recommendations can be made. Selective reporting of study results may impair clinical decision-making. We, therefore, analysed whether the results of completed registered clinical studies in patients with paediatric ED are publicly available or remain unpublished. - Design Cross-sectional analysis. - Setting ClinicalTrials.gov and ClinicalTrialsRegister.eu. - Participants and outcome measures We determined the proportion of published and unpublished studies registered at ClinicalTrials.gov and ClinicalTrialsRegister.eu that were marked as completed by 1st September 2018. The major trial and literature databases were used to search for publications. In addition, the study investigators were contacted directly. For published trials, time to publication was calculated as the difference in months between study completion date and publication date. - Results Of the 44 registered studies on paediatric ED, only 24 (54%) were published by September 2019. Published trials contained data from n=2556 patients, whereas n=1644 patients were enrolled in unpublished trials. Median time to publication was 19 months. Studies completed in recent years were published faster, but still only 9 of 24 trials were published within 12 months of completion. - Conclusion There is a distinct publication gap in clinical research in paediatric ED that may have an impact on meta-analyses and clinical practice.
Gesehen am 19.11.2020